Syntaxin-4 and SNAP23 are involved in neutrophil degranulation, but not in the release of mitochondrial DNA during NET formation - Gigon, Lea; Fettrelet, Timothée; Miholic, Marta; McLeish, Kenneth R.; Yousefi, Shida; Stojkov, Darko; Simon, Hans-Uwe (Frontiers in Immunology, 2023)
Neutrophils are a specialized subset of white blood cells, which have the ability to store pre-formed mediators in their cytoplasmic granules. Neutrophils are well-known effector cells involved in host protection against pathogens through diverse mechanisms such as phagocytosis, degranulation, extracellular traps, and oxidative burst. In this study, we provide evidence highlighting the significance of the SNARE proteins syntaxin-4 and synaptosomal-associated protein (SNAP) 23 in the release of azurophilic granules, specific granules, and the production of reactive oxygen species in human neutrophils. In contrast, the specific blockade of either syntaxin-4 or SNAP23 did not prevent the release of mitochondrial dsDNA in the process of neutrophil extracellular trap (NET) formation. These findings imply that degranulation and the release of mitochondrial dsDNA involve at least partially distinct molecular pathways in neutrophils.